¿The industrial users of the Rionegro’s Free Zone humanice the logistics? - Lukau Quintero, Claudia Elena (2019)
The trade plays a very important role in the development of the country or the region, the governments to promote de external demand, the competitiveness and industrialization, begins to impulse the free zone, with the help the logistics, allows to make the effectiveness and efficiency in the products that are developed inside the business, with most of them cases, the show a hierarchical structure, vertical and pyramidal; by that means, the employees can not make operative decisions in day to day, but when implemented strategies focused in the improvement of the quality of life in the employees shows an improvement in the personal productivity. on the other hand, the logistic by heir agility in the operations requires a leader that identifies the strengths and human resources and thereby potentiate team work. so a question arises ¿if the industrial users of the Rionegro’s free zone promotes good treatment, generating team harmony, where the person is the most important resource for the organization.